REGULATION OF SINGLE-ORGAN NIGHTLIFE IN TANGGAMUS REGENCY THROUGH REGIONAL REGULATION NUMBER 05 OF 2017 CONCERNING THE REGULATION OF PUBLIC ENTERTAINMENT - Suseto, Al Ikhsan Bayu; Saputra, Edi; Talib, Anggi Ahmad (Journal of Learning on History and Social Sciences, 2024)
This article discusses the regulation of single-organ nightlife in Tanggamus Regency through the implementation of Regional Regulation Number 05 of 2017 concerning Public Entertainment Regulation. This study aims to evaluate the effectiveness of these regulations in overcoming social and legal problems arising from nightlife. Single-organ nightlife in Tanggamus often causes disturbances of public order, disturbing noise, and even criminal acts such as drug abuse and fights. To overcome this problem, the Tanggamus Regency Government issued a Regional Regulation that aims to order and regulate entertainment activities tonight. The research method used is a qualitative method with a descriptive approach. The data was collected through in-depth interviews with various related parties, including nightlife business actors, law enforcement officials, and the surrounding community. In addition, document analysis was carried out to understand the content and context of Regional Regulation Number 05 of 2017. The results of the study show that even though the regulation has been implemented, the level of legal awareness among the public and nightlife business actors is still low. Many business actors have not complied with existing regulations, such as operating beyond the predetermined time limit, noise levels that exceed the threshold, and the absence of supervision of illegal activities that occur in their premises. This low legal awareness is caused by several factors, including the lack of socialization and education about the importance of complying with this regulation. Socialization carried out by local governments often does not reach all levels of society and nightlife business actors, so information about this regulation is not spread evenly. In addition, law enforcement that is not strict is also a factor causing low compliance with regulations. Law enforcement officials often compromise on violations that occur, both due to pressure from certain parties and due to a lack of resources to carry out effective law enforcement. Additional measures are needed to increase the effectiveness of law enforcement against these regulations. These measures include increasing socialization and legal education, as well as stricter and more consistent law enforcement. In addition, there is a need for periodic evaluations of the effectiveness of these regulations and adjustments to law enforcement strategies in accordance with conditions and needs in the field. Thus, it is hoped that this regulation can be more effective in regulating single-organ nightlife in Tanggamus Regency and improving order and environmental security.